Biochemical and Histopathological Evaluation of the Radioprotective Effects of Melatonin Against Gamma Ray-Induced Skin Damage - Shabeeb, Dheyauldeen; Najafi, Masoud; Musa, Ahmed E.; Keshavarz, Mansoor; Shirazi, Alireza; Hassanzadeh, Gholamreza; Hadian, Mohammed Reza; Samandari, Hedayat (Current Radiopharmaceuticals, 2019)
Background: Radiotherapy is one of the treatment methods for cancers using ionizing radiations. About 70% of cancer patients undergo radiotherapy. Radiation effect on the skin is one of the main complications of radiotherapy and dose limiting factor. To ameliorate this complication, we used melatonin as a radioprotective agent due to its antioxidant and anti-inflammatory effects, free radical scavenging, improving overall survival after irradiation as well as minimizing the degree of DNA damage and frequency of chromosomal abrasions. Methods: Sixty male Wistar rats were randomly assigned to 4 groups: control (C), melatonin (M), radiation (R) and melatonin + radiation (MR). A single dose of 30 Gy gamma radiation was exposed to the right hind legs of the rats while 40 mg/ml of melatonin was administered 30 minutes before irradiation and 2 mg/ml once daily in the afternoon for one month till the date of rat’s sacrifice. Five rats from each group were sacrificed 4, 12 and 20 weeks after irradiation. Afterwards, their exposed skin tissues were examined histologically and biochemically. Results: In biochemical analysis, we found that malondialdehyde (MDA) levels significantly increased in R group and decreased significantly in M and MR groups after 4, 12, and 20 weeks, whereas catalase (CAT) and superoxide dismutase (SOD) activities decreased in the R group and increased in M and MR groups during the same time periods compared with the C group (p<0.05). Histopathological examination found there were statistically significant differences between R group compared with the C and M groups for the three different time periods (p<0.005, p<0.004 and p<0.004) respectively, while R group differed significantly with MR group (p<0.013). No significant differences were observed between C and M compared with MR group (p>0.05) at 4 and 20 weeks except for inflammation and hair follicle atrophy, while there were significant effects at 12 weeks (p<0.05). Conclusion: Melatonin can be successfully used for the prevention and treatment of radiation-induced skin injury. We recommend the use of melatonin in optimal and safe doses. These doses should be administered over a long period of time for effective radioprotection and amelioration of skin damages as well as improving the therapeutic ratio of radiotherapy.
Keywords: oxidative stress